LISTENING WITH A SMILE: HOW HUMOR ENHANCES STUDENT ENGAGEMENT IN EFL COURSES - Damanik, Sisila Fitriany; Hutasuhut, Mahmud Layan; Andayani, Widya; Nasution, Nazlah Syahaf (University of Kuningan, 2025)
The use of humor in English as a Foreign Language (EFL) classrooms has gained increasing attention due to its potential to enhance learning outcomes. Research has shown that humor can improve student motivation, engagement, and comprehension by reducing anxiety and creating a more relaxed learning atmosphere. However, little is known about the effectiveness of humor in EFL listening courses within the Indonesian context, particularly in hierarchical learning environments where teacher-centered instruction is dominant. This study aims to explore the perceptions of English Literature students at Universitas Negeri Medan (Unimed) regarding the use of humor in listening courses and to analyze its impact on motivation, engagement, and listening comprehension. The study employed a qualitative approach with a descriptive design, involving 56 students from two Intermediate Listening Comprehension classes. Data were collected through observations, questionnaires, and semi-structured interviews, and analyzed using thematic analysis. The results indicate that humor positively influences listening comprehension and enhances motivation and engagement. Students reported that humor made listening activities more enjoyable and increased their willingness to participate. However, cultural sensitivity, linguistic complexity, and the lack of structured training for lecturers were identified as challenges in implementing humor effectively. The findings suggest that incorporating contextually relevant humor into listening instruction can create a more engaging learning environment and improve student outcomes. Future research should explore the long-term effects of humor through experimental and cross-cultural studies to strengthen the understanding of humor’s role in EFL education.